The SCUBA-2 Cosmology Legacy Survey: blank-field number counts of 450um-selected galaxies and their contribution to the cosmic infrared background - Geach, J; Chapin, E; Coppin, K; Dunlop, J; Halpern, M; Smail, I; Werf, P; Serjeant, S; Farrah, D; Roseboom, I; Targett, T; Arumugam, V; et al. (2012)
The first deep blank-field 450um map (1-sigma~1.3mJy) from the SCUBA-2 Cosmology Legacy Survey (S2CLS), conducted with the James Clerk Maxwell Telescope (JCMT) is presented. Our map covers 140 arcmin^2 of the COSMOS field, in the footprint of the HST CANDELS area. Using 60 submillimetre galaxies (SMGs) detected at >3.75-sigma, we evaluate the number counts of 450um-selected galaxies with flux densities S_450>5mJy. The 8-arcsec JCMT beam and high sensitivity of SCUBA-2 now make it possible to directly resolve a larger fraction of the cosmic infrared background (CIB, peaking at ~200um) into the individual galaxies responsible for its emission than has previously been possible at this wavelength. At S_450>5mJy we resolve (7.4[+/-]0.7)x10^-2 MJy/sr of the CIB at 450um (equivalent to 16[+/-]7% of the absolute brightness measured by COBE at this wavelength) into point sources. A further ~40% of the CIB can be recovered through a statistical stack of 24um emitters in this field, indicating that the majority (~60%) of the CIB at 450um is emitted by galaxies with S_450>2mJy. The average redshift of 450um emitters identified with an optical/near-infrared counterpart is estimated to be <z>=1.3, implying that the galaxies in the sample are in the ultraluminous class (L_IR~1.1x10^12 L_sun). If the galaxies contributing to the statistical stack lie at similar redshifts, then the majority of the CIB at 450um is emitted by galaxies in the LIRG class with L_IR>3.6x10^11 L_sun.</z>